Ponticulus Posticus- The “Aching” Bridge - Mohan, Vinay; Shivakshi Chansoria, Shruti Chauhan, Vihang Naphade,; Garg, Neha (International Journal of Innovative Research in Medical Science, 2017)
The Ponticulus posticus is a bony bridge located in the posterior arch of the atlas. It houses the passage of the vertebral artery. Its presence has been associated with development of cervical pain, migraine and diplopia, to name a few. The purpose of this study was to assess its prevalence in asymptomatic patients. We examined 500 digital lateral cephalograms of patients aged from 16 to 28 years. 16% of cases, showed some degree of ossification. As indicated by this study, it is a not an uncommon anomaly in the Indian population. Thus, care must be taken to account for it on lateral cephalograms of patients. If any such anomaly is detected or suspected, it must be documented in the patient’s health record and specialist consultation must be sought.